Evidence for a Gender-Related Effect of Alcoholism on Brain Volumes - Hommer, Daniel W.; Momenan, Reza; Kaiser, Erica; Rawlings, Robert R. (The American journal of psychiatry, 2001)
OBJECTIVE: The goal of this study was to compare brain volumes of alcoholic and nonalcoholic men and women and determine if the magnitudes of differences in brain volumes between alcoholic women and nonalcoholic women are greater than the magnitudes of the differences between alcoholic men and nonalcoholic men. METHOD: The study group included 118 subjects: 79 inpatients 30-60 years of age who were alcohol dependent but had no clinically apparent cognitive impairment or medical illness (43 men and 36 women) and 39 healthy comparison subjects of similar age who were not alcoholic (20 men and 19 women). The volume of intracranial contents was segmented into gray matter, white matter, sulcal CSF, and ventricular CSF from a T1-weighted magnetic resonance image obtained after the alcoholic subjects had attained 3 weeks of sobriety. RESULTS: Alcoholic women had significantly smaller volumes of gray and white matter as well as greater volumes of sulcal and ventricular CSF than nonalcoholic women. The differences in gray and white matter volumes between alcoholic and nonalcoholic men were significant, but the significance of these differences was of a smaller magnitude than the significance of the differences between alcoholic and nonalcoholic women. Direct comparisons of alcoholic men and women showed that the proportion of intracranial contents occupied by gray matter was smaller in alcoholic women than in alcoholic men. The magnitudes of differences in brain volumes adjusted for intracranial size between alcoholic women and nonalcoholic women were greater than the magnitudes of the adjusted differences between alcoholic men and nonalcoholic men. CONCLUSIONS: These results are consistent with greater sensitivity to alcohol neurotoxicity among women.